Analysis of Revenue Accounting Information Systems And Cash Disbursements (Case Study on Alfamart Franchise CV Lintang Alfaria) - Hidayat, Rahmat; Kartini, Tina; Indrawan, Andri (Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to find out how the cash receipts and disbursement accounting information system at the Alfamart franchise CV Lintang Alfaria. Data analysis used is qualitative data with qualitative descriptive analysis method. The results showed that the cash receipts and disbursements accounting information system at CV Lintang Alfaria still uses manual standards in its financial reporting.